URGENSI PEMBENTUKAN KOMISI ETIK KECERDASAN ARTIFISIAL (AI) DI INDONESIA - Mendrofa, Idaman Jaya; Gultom, Elfrida Ratnawati; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Abstract: To ensure that AI technology is used in a way that is beneficial and does not harm society, this study aims to investigate the need for Indonesia to establish an Artificial Intelligence (AI) Ethics Commission. The main issue raised in this study is whether Indonesia needs to immediately establish an AI Ethics Commission. The methodology used is normative research with descriptive analysis, and secondary data is collected from various legal sources and related literature. Based on the research findings, an ethics commission is very important to monitor and enforce the AI code of ethics in accordance with the regulations of the National Science and Technology System Law (UU IPTEK). In short, the establishment of an Artificial Intelligence Ethics Commission will encourage the ethical use of AI and reduce the possibility of misuse of technology. The establishment of this commission is suggested by this study as a calculated step to support moral standards in the use of AI in Indonesia.Keywords: Urgency, Ethics Commission, Artificial Intelligence